The Medium Effect on the Selective Complexation of Mercury (II) and Silver (I) by a Fully Substituted Lower Rim Calix[4]arene Receptor - Aragon, Walther B. Aparicio; Namor, Angela F. Danil de (IJRDO-Journal of Applied Science, 2018)
Mercury has been recognized as a highly dangerous element by the Environmental Protection Agency (EPA) due to its accumulative and persistent character in the environment and biota. In the Latin American region several countries are affected by the extremely high contents of mercury in the environmental and consequently in water, therefore the aim of this research is to synthesize receptors able to interact selectively with mercury species.This paper reports the synthesis of a novel lower rim calix[4]arene derivative with pendent arms containing oxygen, phosphorus and sulphur as donor atoms, (1). Spectrometric (1H NMR) measurements were performed to determine the actives site of complexation of this ligand and the mercury (II) and silver (I) cations in solution. Conductance data provide information regarding the composition of the metal-ion complex in acetonitrile and methanol. The stability constant of the mercury (II) and silver (I) complex was derived from direct potentiometric titration. The latter technique was also used to characterize the thermochemical character of the binding process